ANALISIS PANDANGAN PESERTA DIDIK TERHADAP POLA INTERAKSI GURU DALAM PEMBELAJARAN DI MAS AMALIYAH SUNGGAL - Amanda Putri Ramadhani T; Indah Putri Sari; Alfi Syahri; Muhammad Putra Dinata (Jurnal Al-Fatih, 2022)
This study was to describe students' views on the pattern of teacher interaction that occurred in Pancasila and Citizenship Education (PPKN) learning in class X MAS Amaliyah Sunggal, using the BIAS (Brown Interaction Analysis System) interaction analysis. The approach used is an approach with a descriptive method. The research subjects were teachers and students in class X MAS Amaliyah Sunggal. The object of the research is the students' view of the teacher's interaction pattern in learning Civics. Data collection techniques used are observation techniques, interviews. The results of the study explain that the tendency of categories that appear in learning activities in class X IPA and X IPS have differences. Based on Brown's seven categories, the categories that appear in PPKN learning in class X science are the student response category (Pupil Response (PR) where students talk more both commenting and asking questions, the interaction that occurs is a two-way interaction, this is related to speaking skills and material. categories taught. In class X Social Sciences, what appears is the category of teacher questions (Teacher Questions (TQ) where the teacher is more dominant in asking questions to students. The interaction that occurs is a two-way interaction because when the teacher asks some questions the teacher asks questions. However, it is only limited to between teachers and students or students with teachers Interactions that occur are related to the subject matter being taught and the skills that must be achieved by students after learning is complete